Changes in reproductive behavior associated with the perception and individual experiences of the COVID-19 pandemic - Slabá, Jitka (PloS one, 2023)
This study evaluates the impacts of the COVID-19 pandemic on the reproductive behavior of men and women during the most restrictive period of the pandemic in Czechia. At the end of this period, data was collected for the Czech GGS COVID Pilot-Follow-up Study (April 2021), which included additional questions on reproductive plans and perceptions of the pandemic related to fertility. The study focuses in detail on the evaluation of the favorability of fertility during this period by considering the impact of the pandemic on the lives of individuals in various life areas. It subsequently attempts to determine to what extent this evaluation and personal experiences of the pandemic affected reproductive behavior (the intended number of children, current attempts to conceive and short-term fertility intentions). In summary, in most cases the respondents considered the most severe period of the pandemic to be unfavorable in terms of childbirth. Women provided an overall negative assessment of the favorability of childbirth in this period, which was reflected in a reduction in the planned number of children, while the men who considered this period favorable declared a higher chance of short-term fertility intentions.
Keywords: Perception; Child; Follow-Up Studies; následné studie; dítě; Male; Pandemics; percepce; lidé; Female; mužské pohlaví; ženské pohlaví; pandemie; Humans; Reproductive Behavior; COVID-19; reprodukční chování